A new high-speed visual stimulation method for gaze-contingent eye movement and brain activity studies - Richlan, Fabio; Gagl, Benjamin; Schuster, Sarah; Hawelka, Stefan; Humenberger, Josef; Hutzler, Florian (Frontiers in Systems Neuroscience, 2013)
Approaches using eye movements as markers of ongoing brain activity to investigate perceptual and cognitive processes were able to implement highly sophisticated paradigms driven by eye movement recordings. Crucially, these paradigms involve display changes that have to occur during the time of saccadic blindness, when the subject is unaware of the change. Therefore, a combination of high-speed eye tracking and high-speed visual stimulation is required in these paradigms. For combined eye movement and brain activity studies (e.g., fMRI, EEG, MEG), fast and exact timing of display changes is especially important, because of the high susceptibility of these methods to visual stimulation. Eye tracking systems already achieve sampling rates up to 2000 Hz, but recent LCD technologies for computer screens reduced the temporal resolution to mostly 60 Hz, which is too slow for gaze-contingent display changes. We developed a high-speed video projection system, which is capable of reliably delivering display changes within the time frame of < 5 ms. This could not be achieved even with the fastest CRT monitors available (< 16 ms). The present video projection system facilitates the realization of cutting-edge eye movement research requiring reliable high-speed visual stimulation (e.g., gaze-contingent display changes, short-time presentation, masked priming). Moreover, this system can be used for fast visual presentation in order to assess brain activity using various methods, such as electroencephalography (EEG) and functional magnetic resonance imaging (fMRI). The latter technique was previously excluded from high-speed visual stimulation, because it is not possible to operate conventional CRT monitors in the strong magnetic field of an MRI scanner. Therefore, the present video projection system offers new possibilities for studying eye movement-related brain activity using a combination of eye tracking and fMRI.